Assessment of the frequency of cardiovascular risk factors in patients with Takayasu's arteritis - ÇIKIKÇI, CEYLAN; ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2017)
Objectives. The prevalence of atherosclerotic risk factors and disease in Takayasu's arteritis (TAK) has not been well defined. We aimed to assess the frequency of cardiovascular (CV) risk factors and the incidence of CV events (CVEs) in patients with TAK from two ethnically different populations. Methods. Patients with TAK followed at Mayo Clinic, Rochester, MN, USA and Marmara University, Istanbul, Turkey were included in this retrospective study. Patients with TAK were compared with age-, sex- and calendar year-matched controls from the same geographical region without TAK. The 2008 Framingham 10-year general CV risk score (FRS) was used for the evaluation of CV risk at the time of TAK incidence/index date. Results. In total, 191 patients with TAK and 191 non-TAK controls were included. Hypertension and the prevalence of lipid-lowering treatments were significantly more frequent in TAK. Prior to the incidence/index date, occurrence of CVE was significantly higher in TAK. The FRS was significantly higher in TAK compared with non-TAK at incidence/index date. The cumulative incidence of CVE was 15.4% at 10 years in TAK vs 5.8% in non-TAK; the risk of CVE was increased among patients with TAK (hazard ratio = 4.36; 95% CI: 1.25, 15.13). Conclusion. CV risk factors are more common in patients with TAK, particularly hypertension. The FRS is higher in patients with TAK at the time of diagnosis. The cumulative incidence of CVE was also significantly higher during follow-up in TAK. Our results suggest that patients with TAK should undergo careful assessment of CV risk factors, and an aggressive risk modification approach is warranted.
Keywords: Takayasu's arteritis; atherosclerotic risk; cardiovascular event; GIANT-CELL ARTERITIS; AUSTRALIAN POPULATION; RHEUMATOID-ARTHRITIS; ISCHEMIC EVENTS; DISEASE; ATHEROSCLEROSIS; CLASSIFICATION; MORTALITY; DIAGNOSIS; CRITERIA